2016
DOI: 10.1002/cam4.661
|View full text |Cite
|
Sign up to set email alerts
|

High expression of TRF2, SOX10, and CD10 in circulating tumor microemboli detected in metastatic melanoma patients. A potential impact for the assessment of disease aggressiveness

Abstract: Circulating tumors cells (CTCs) can be detected in the blood of metastatic melanoma patients (MMPs) both as isolated circulating tumor cells (iCTCs) and circulating tumor microemboli (CTMs), but their clinical significance remains unknown. The aim of this work was to evaluate the prognostic impact in metastatic cutaneous melanoma of CTMs and iCTCs identified by a cytomorphological approach using the isolation by size of tumor cell (ISET) method. We characterized the phenotype of CTCs using anti‐PS100, anti‐SOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Moreover, CTM was captured by this size-based platform, and CTM-positive patients with advanced CRC had worse survival than isolated CTCs-positive patients. It was reported that tumor cells within CTM could be protected from anoikis and were relatively resistant to cytotoxic drugs [35], and CTM was an independent prognostic factor [35, 36]. Hence, CTM would be more malignant and aggressive than isolated CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CTM was captured by this size-based platform, and CTM-positive patients with advanced CRC had worse survival than isolated CTCs-positive patients. It was reported that tumor cells within CTM could be protected from anoikis and were relatively resistant to cytotoxic drugs [35], and CTM was an independent prognostic factor [35, 36]. Hence, CTM would be more malignant and aggressive than isolated CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…According to cytopathological criteria [16, 30, 111], cancer cells from patients are usually larger than 16 microns. The presence in blood of intact cancer cells smaller than 8 microns, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such cancer cells are expected to be of clinical interest [2, 4] as shown by independent clinical studies using ISET ® [3, 17, 18, 22, 24, 26, 35, 103, 111115] (Reviewed in Table H in S1 File). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neutral endopeptidase and/or neprilysin), and legumain (EC 3.4.22.34; syn. asparaginyl endopeptidase) (33)(34)(35)(36). However, on the basis of only few current data, their usefulness as biomarkers still is difficult to estimate.…”
Section: Other Enzyme Markersmentioning
confidence: 99%